Assessment of orthoimage and DEM derived from ZY-3 stereo image in Northeastern China. Issue 349 (3rd July 2016) - Dong, Y.; Chen, W.; Chang, H.; Zhang, Y.; Feng, R.; Meng, L.
Abstract : ZiYuan-3 (ZY-3, meaning Resource-3) is China's first civilian multispectral satellite with high-resolution stereo mapping capability. The along-track stereo images of ZY-3 allow the generation of digital elevation models (DEMs) for various mapping applications. This article evaluated the precision of the derived stereo DEM and orthoimages of ZY-3 data for a test site in Northeastern China. Pixel offset and GPS survey data were used to evaluate the image products. Orthoimages were derived by incorporating rational polynomial coefficients (RPCs) of the satellite orbits and the reference DEMs, including the Advanced Spaceborne Thermal Emission and Reflection Radiomete (ASTER) global digital elevation model (GDEM) and ZY-3 stereo elevation model. The generations of orthoimages were categorised into four approaches depending on the RPCs, control points and/or reference DEMs used. When only the ASTER GDEM was used, the derived orthoimages of the forward and backward viewing sensors showed clear pixel offsets against the GPS check points (CKPs). For example, the offsets of the orthoimage derived using forward-looking image were 13·58 and 26·50 m, in x (easting) and y (northing) directions, respectively. These results also indicated that the pixel offset vectors between the forward and backward orthoimages was systematic which was caused by the error in the RPCs. The second and third approaches were to generate the ZY-3 stereo DEMs first, with and without the use of ground control points (GCPs), and then used the stereo DEMs to generate the orthoimages of the forward and backward looking images. The forth approach used both GCPs and ASTER GDEM to generate the orthoimages. The results showed the use of four GCPs in the process improved the accuracy of the orthoimages. Therefore, ZY-3 can deliver the DEM and orthoimage products to meet the accuracy requirement of the national 1 : 50 000 mapping with four well distributed GCPs.